2020
DOI: 10.3390/nu12082399
|View full text |Cite
|
Sign up to set email alerts
|

Changing Dietary Habits in Veneto Region over Two Decades: Still a Long Road to Go to Reach an Iodine-Sufficient Status

Abstract: Background: Fifteen years after a nationwide voluntary iodine prophylaxis program was introduced, the aims of the present study were: (a) to obtain an up-to-date assessment of dietary iodine intake in the Veneto region, Italy; and (b) to assess dietary and socioeconomic factors that might influence iodine status. Methods: Urinary iodine concentration (UIC) was obtained in 747 school students (median age 13 years; range: 11–16 years). Results: The median UIC was 111 μg/L, with 56% of samples ≥ 100 μg/L, but 26%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Apparently, the proportion of UIC values <50 µg/L was 23% for women, which is above the recommendation that no more than 20% of the participants should be below 50 µg/L. Even when adjusted for the potential dilution effect from large urine volumes of about 1.8 L in women to the normalized mean volume of 1.5 L, the median UIC (76 µg/L) is still below the current WHO criteria [33].…”
Section: Iodine Intake As Compared With Recommendationsmentioning
confidence: 68%
“…Apparently, the proportion of UIC values <50 µg/L was 23% for women, which is above the recommendation that no more than 20% of the participants should be below 50 µg/L. Even when adjusted for the potential dilution effect from large urine volumes of about 1.8 L in women to the normalized mean volume of 1.5 L, the median UIC (76 µg/L) is still below the current WHO criteria [33].…”
Section: Iodine Intake As Compared With Recommendationsmentioning
confidence: 68%
“…The iodine status in Italy has also been investigated, using spot urine sampling, in some recent local studies relative to a few Italian regions. For example, in Veneto, a region in the north-east of Italy, a study carried out in 2018 and 2019 within the OSNAMI survey, on 747 school-age children with an average age of 13 years showed that in the entire cohort the median UIC was 111 µg/L (thus, within the range of adequacy set by WHO), yet 26% of the participants had a UIC below 50 µg/L [ 24 ]. The UIC was significantly higher among the iodized salt users than among non-users (117 versus 90 µg/L) as well as among regular consumers of cow’s milk compared with occasional consumers (132 vs. 96 µg/L): these results suggest that only the combined regular intake of cow’s milk and use of iodized salt allowed an adequate iodine status [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Veneto, a region in the north-east of Italy, a study carried out in 2018 and 2019 within the OSNAMI survey, on 747 school-age children with an average age of 13 years showed that in the entire cohort the median UIC was 111 µg/L (thus, within the range of adequacy set by WHO), yet 26% of the participants had a UIC below 50 µg/L [ 24 ]. The UIC was significantly higher among the iodized salt users than among non-users (117 versus 90 µg/L) as well as among regular consumers of cow’s milk compared with occasional consumers (132 vs. 96 µg/L): these results suggest that only the combined regular intake of cow’s milk and use of iodized salt allowed an adequate iodine status [ 24 ]. In Liguria, a region of north-west Italy, the median UIC values detected in adult subjects during the periods 2009–2013 and 2014–2018 were, respectively, 105 and 98 µg/L, indicating only a marginal iodine sufficiency in this region fourteen years after the enactment of law 55/2005 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, iodine excess can be also found, mostly due to high iodine content in tap water [48][49][50][51]. In many countries (Continental Europe, the UK and the US), the primary sources of iodine are dairy products and fortified table salt [52][53][54][55][56][57]. Elsewhere, especially in the Middle East, dietary iodine mainly comes from fortified flour and salt [58].…”
Section: Discussionmentioning
confidence: 99%